SOME ANALYSIS ASPECTS OF COMMODITY MARKET DEVELOPMENT - Lyudmila V. Borisova; Valery P. Dimitrov; Natalia P. Semenyuk (Advanced Engineering Research)
Some questions of the development of the commodity turnover and interregional relations of the Rostov region are considered. Certain statistical data whose analysis permits to estimate current commodity market tendencies is given. Commodity markets monitoring contributes to formulating specific actions on the investment prospects of the Rostov region.